The impact of television advertision on the consumption behavior of youth. " Afield study on a sample of thestudents of the department of sociologies in tishreen University " - Zreika, Yousra; Makragoni, Boushra (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The progress and development of commercial enterprises and the multiplicity of industrial and service activities, opened up broad areas of growth for countries, leading to a large and clear diversity in goods and services. This has made it necessary to find a way to link the product to the consumer, And as the most widespread media, As Advertising occupies space of media, especially television. This gave it a feature of promotion among the different means . The current research deals with the role of television advertisting in the consumer behavior of young people, To achieve the research objectives, aquestionnaire was designed. the results of the study were presented according to the variables presented, that there is a statistically significant relationship between watching television ADS and growing consumer behavior according to gender variable, especially for females at the level of significance( 0,001) There were no statistically significant differences between the growth of consumer behavior and the variable" age group" at the level of significance(0,001), The Anova test was used to analyze the data statistically.